The Image of Islam in Foreign Media Frames Facing the Spread of Covid-19 Pandemic - Zakiah, Kiki; ., Askurifai; ., Hasbiansyah; Anjali, Millenia (KnE Social Sciences, 2023)
The Covid-19 pandemic has had a profound impact on various aspects of life, including religious practices. In the realm of foreign media, Islam has often been portrayed negatively, particularly in political news. Throughout the Covid-19 pandemic, which began in 2020 and continues to the present, the media has actively covered all aspects related to Covid-19, including those related to Islamic religious practices. However, the image of Islam presented in these media reports is not always as negative and intimidating as it is often portrayed. This study aims to explore how the image of Islam is portrayed in foreign media during the Covid-19 pandemic. The research utilizes the Robert N Entman framing analysis method to thoroughly analyze the underlying messages conveyed in foreign media news concerning Islam’s image amid the pandemic. Three news texts from different foreign online media sources; theconversation.com, print.in, and cnn.com, were examined. The analysis of the three news texts reveals that foreign media presents a positive image of Islam in the context of the Covid-19 pandemic from various perspectives. These perspectives include highlighting Islamic hygiene practices, the attitudes of adherents towards health measures, and other aspects of worship traditions. Keywords: image, Islam, foreign media, framing analysis